A signal-to-noise-ratio-based analysis of multifocal visual-evoked potentials in multiple sclerosis risk assessment. Issue 2 (February 2016) - De Santiago, L.; Ortiz del Castillo, M.; Blanco, R.; Barea, R.; Rodríguez-Ascariz, J.M.; Miguel-Jiménez, J.M.; Sánchez-Morla, E.M.; Boquete, L.
Highlights: Assessment of MS patients' visual function was improved by using signal-to-noise ratio (SNR) values at ring 5. Multifocal visual-evoked potentials' (mfVEPs) SNR values decreased as risk of developing MS increased. MfVEPs' ring 5 eccentricity amplitude was related to disability severity in MS patients. Abstract: Objective: To study the value of using the signal-to-noise ratio (SNR) of multifocal visual-evoked potentials (mfVEPs) in assessment of subjects at risk of developing multiple sclerosis (MS). Methods: MfVEP signals were obtained from 15 patients with radiologically isolated syndrome (RIS), from 28 patients with clinically isolated syndrome (CIS), from 28 with clinically definite MS and from 24 control subjects. The CIS and MS groups were divided into two subgroups: those with eyes affected by optic neuritis (ON) and those without (non-ON). The mfVEPs' SNR was obtained for both the whole visual field and at various eccentric rings. The area under the curve (AUC) was calculated by comparing the control subjects' mfVEP SNR values with those of the RIS, CIS and MS groups. Results: In whole visual field analysis, risk of developing MS increased as SNR decreased (SNRCONTROL  = 0.70, SNRRIS  = 0.62, SNRCIS-nonON  = 0.54, SNRCIS-ON  = 0.40, SNRMS-nonON  = 0.52, SNRMS-ON  = 0.40). Ring 5 (9.8°–15° eccentricity) was most affected by the SNR decrease, as indicated by its higher AUC values (AUCFULL_EYE  = 0.81, AUCRING_5  = 0.89). A significant relationship (Spearman correlation, ρ RING_5  = 0.61) between SNR values and disability severity on the Expanded Disability Status Scale (EDSS) was observed in clinically definite MS patients. Conclusion: A new method based on analysis of the SNR of mfVEP signal amplitude improves assessment of patients at risk of developing MS. Significance: Improved mfVEP assessment of MS-risk patients was achieved by using SNR values at 9.8°–15° eccentricity of the visual field.